The Oman Flora and Fauna Survey, 1975 - Harrison, David L. (Journal of Oman Studies, 1975)
The story of this expedition has its origin in the concern which has developed in recent years for the future of the Arabian Tahr (Hemitragus jayakari). This unique species of wild goat, confined to the mountain ranges of Oman, seemed to be threatened with extinction. During the spring of 1973 we formulated a plan for a National Park in the Jebel Akhdar Range. The area we selected is centred on the principal peak of Jebel Akhdar, and is almost rectangular, about 50 km across and 30 km from north to south, in the Hajar al-Gharbi, just south of Rostaq.
Keywords: Botanique -- Oman

Wild flowers of Northern Oman - Mandaville, James Jr. (Bartholomew Books, 1978)
Keywords: Botanique -- Oman

Plants of Dhofar, the southern region of Oman: traditional, economic and medicinal uses - Miller, Anthony G.; Morris, Miranda (Diwan of Royal Court, 1988)
Keywords: Botanique -- Oman

Wild flowers of Northern Oman (Bartholomew Books, 1978)
Keywords: Botanique -- Oman

Interim report on the results of the Oman flora and fauna survey 1975 (Ministry of Diwan Affairs, 1976)
Keywords: Botanique -- Oman

The Scientific results of the Oman Flora and Fauna Survey, 1977 (Dhofar) (Journal of Oman Studies. Special report, 1980)
Keywords: Botanique -- Oman

The Scientific results of the Oman Flora and Fauna Survey, 1975 (Journal of Oman Studies. Special report, 1977)
Keywords: Botanique -- Oman